Pengujian Trilemma Conditions pada Perekonomian Indonesia - Yunita, Mela; Achsani, Noer Azham; Anggraeni, Lukytawati (UI Scholars Hub, 2017)
The key challenge for monetary policy in emerging market countries is simultaneously maintain monetary independence, exchange rate stability, and join with financial integration. This research explain the interaction of monetary policy in Indonesia over time to answer those three challenge with a Trilemma conditions. This research evaluate the Bank Indonesia’s decision to change the exchange rate regime and applied ”inflation targeting”. The methods include to build the Trilemma’ index and testing the Trilemma with constant regression. The results indicate that Bank Indonesia has tradeoff in determining the combination of monetary policy objectives. Tradeoff for Bank Indonesia more heavy under free floating due to fear of floating’s problem and tradeoff lighter when inflation targeting applied.